Does the Treatment After Kasai Procedure Influence Biliary Atresia Outcome and Native Liver Survival?. Issue 4 (October 2020) - Pietrobattista, Andrea; Mosca, Antonella; Liccardo, Daniela; Alterio, Tommaso; Grimaldi, Chiara; Basso, MariaSole; Saffioti, Maria Cristina; Corte, Claudia Della; Spada, Marco; Candusso, Manila
ABSTRACT: Objectives: Biliary atresia (BA) is a rare and progressive idiopathic disease affecting the biliary tract that can lead to end-stage liver disease. The main treatment is Kasai portoenterostomy (KP). The use of adjuvant therapy (AT; prophylactic antibiotics and steroids) after KP aims to prevent cholangitis and reduce the need for liver transplantation (LT), but there is a lack of evidence on their effectiveness. We investigated the impact of significant changes in the post-KP protocol on the overall outcomes of BA. Methods: We enrolled 43 consecutive infants undergoing KP at Bambino Gesù Children's Hospital between July 2012 and October 2018. We compared AT (AT group; n=25) against no treatment (AT-free group; n = 18). Results: No significant differences in anthropometric and laboratory parameters were shown between the 2 groups at baseline and every study evaluation (1, 3, and 6 months). The incidences of clinical complications of liver disease were similar. Six months post-KP, the achievement of serum total bilirubin ⩽1.5 mg/dL and satisfactory Pediatric End-Stage Liver Disease scores were not significantly different between the 2 groups. Cholangitis was observed in 30% of patients in the first 6 months postoperatively: 33% and 28% in the AT-free and AT groups, respectively ( P  = 0.18). Survival to LT listing at 12 months and without LT at 24 months were not significantly different between the 2 groups ( P  > 0.05). Conclusions: AT after KP confirmed conflicting results; therefore, multicentered, prospective, randomized control studies are needed to better understand its utility after KP, especially in the multidrug resistance spread era. Abstract : Supplemental Digital Content is available in the text